Construccion y analisis de modelos empiricos para la estimacion de la evaporacion en Venezuela - Parra, R.M.=700 1 Cortez, A.; Rodriguez, M.F.; Rey, J.C.; Ovalles, F.; Gonzalez, W.
(Es, En)
ilus., 3 ref.
Keywords: EVAPORACION; ANALISIS ESTADISTICO; VENEZUELA; AGRONOMIA TROPICAL